2018
DOI: 10.1002/jid.3353
|View full text |Cite
|
Sign up to set email alerts
|

Orphanhood, Household Relationships, School Attendance and Child Labor in Zimbabwe

Abstract: The high incidence of orphanhood among children makes Zimbabwe an interesting case to study the school/work decision for children able to attend lower secondary. After controlling for household wealth, covariates at the individual, and household levels, and community fixed effects, I find that orphans are less likely to attend school and more likely to work. While orphans and non‐orphans face the same marginal cost to go to school and work, living in blended households places orphans at a higher disadvantage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Finally, the pandemic has also reduced the long-term demand for education through an increase in the number of orphans. Novella (2018) confirms the last link using a Zimbabwean survey for 2007-8. This revealed that orphans leave (secondary) school early and hence enter the labor market early compared with non-orphans.…”
Section: Labor and Human Capitalsupporting
confidence: 63%
“…Finally, the pandemic has also reduced the long-term demand for education through an increase in the number of orphans. Novella (2018) confirms the last link using a Zimbabwean survey for 2007-8. This revealed that orphans leave (secondary) school early and hence enter the labor market early compared with non-orphans.…”
Section: Labor and Human Capitalsupporting
confidence: 63%
“…The women became the household head due to several problems, such as the household head who had previously died, causing the children to be orphaned. Novella (2018) found that orphans tend to work and not go to school.…”
Section: Resultsmentioning
confidence: 99%
“…Among the Himba in Namibia, Scelza and Silk (2014) found that fostering children out was associated with higher reproductive success for mothers (i.e., a greater number of surviving children), but was associated with an increased risk of stunting and being underweight for foster children. Consistent with the notion that fostering entails some cost to children, several studies have also reported that fostered children are less likely to be enrolled in school (Roby, Erickson, and Nagaishi 2016;Assaad, Levison, and Zibani 2010;Moyi 2010;Novella 2018;Urassa et al 1997).…”
Section: Introductionmentioning
confidence: 85%